PERSEPSI KEPUASAN LAYANAN TRANSPORTASI KERETA API PT. KERETA API INDONESIA (PT.KAI): SURVEY PADA MAHASISWA YANG BERKULIAH DI SURABAYA - Permatasari, Maurisia Putri; Kristanto, Damar; Ervianty, Rizka Miladiah; Salam, Moh. Darus; Fiatiano, Edwin; Dwikesumasari, Phima Ruthia; Zulfa, Vivi Rodliyatuz (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2024)
PT Kereta Api Indonesia (KAI) is a state-owned company which operates in the field of rail transportation services in Indonesia. Even though PT KAI dominates the market share in the railway industry in Indonesia, maintaining qualitu and improving quality remains a top priority for the company. Students studying at various campuses in Surabaya do not only come from within the city, but spread from various cities outside Surabaya which are connected to the railway network. Students are a group of people who have a unique perspective, they are very sensitive to the quality of services provided if they want to use a service so that their views and assessments as users of rail transportation services will be good input for companies, in this case PT KAI. The aim of this research is to determine the level of satisfaction with rail transportation services managed by PT KAI from the perspective of students who are its users. This research succeeded in capturing 476 students from various campuses in Surabaya. The research results show that the majority of service elements are included in the good interval, unfortunately all elements are not included in the very good interval and there are also several elements that are included in the poor interval. This need to be a concern for companies to further improve services, especially those aimed at the student segment.